(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, it is important to organize and conduct the professional practice methodically in order to ensure that students can effectively apply their existing theoretical knowledge in practice, and to ensure that the professional activity skills formed during the education process become qualifications. it is important and about innovative approaches to prepare students for practical pedagogical and management activities by means of professional practice.